The Social Dynamics of Employee Silence: A Qualitative Meta-Synthesis of Organizational Culture, Psychological Safety, and Voice Behavior - Maria Ulfah (Golden Ratio of Mapping Idea and Literature Format, 2025)
Employee silence represents a critical organizational phenomenon wherein employees deliberately withhold work-related ideas, concerns, suggestions, and information from individuals who could effect change. This systematic literature review employs a qualitative meta-synthesis approach to integrate research findings on the social dynamics underlying employee silence, with particular emphasis on the interrelationships among organizational culture, psychological safety, and voice behavior. A comprehensive search of eight academic databases (Scopus, Web of Science, ScienceDirect, Emerald Insight, SpringerLink, Taylor & Francis, Wiley Online Library, and Google Scholar) was conducted using predetermined inclusion and exclusion criteria, yielding 48 studies for final analysis. The thematic synthesis revealed six primary themes: (1) organizational culture as a social context of silence, (2) psychological safety as a mediating mechanism, (3) fear and power distance in defensive silence, (4) leadership and silence climate, (5) voice behavior as a counterforce to silence, and (6) social norms and the institutionalization of silence. The findings demonstrate that employee silence is fundamentally a socially constructed phenomenon shaped by cultural values, power dynamics, leadership behaviors, and communication norms rather than merely an individual decision. The proposed conceptual framework illustrates a pathway wherein organizational culture influences psychological safety, which subsequently affects voice behavior and ultimately determines the prevalence of employee silence. This study contributes to organizational behavior theory by providing an integrated understanding of the social dynamics of silence and offers practical implications for organizational leaders seeking to cultivate speak-up cultures.